(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
The purpose of this study focuses on presenting the food and drink process in the case of making lychee juice and lychee-tea combination fruit juice in a tropical country such as Vietnam. We mainly use methods of qualitative analysis, synthesis and inductive methods, with description and explanatory methods. Authors also use a value chain approach from a material supply (lychee products) to production and market distribution. Research results show us that choosing good red lychee together with good green or black tea, esp. Lipton tea, which is produced from the region of material supplying in the Northern region of Vietnam, then mixed with sugar and ice, using little vegetables will be very good for everybody health, functioning as medical treatment to prevent heart disease, and helps men and women stronger. In the meantime, we also propose lychee and tea planting policies and capital financing policies in the country, esp. In the north of Vietnam. For instance, the nation needs to continue to negotiate with countries that have not yet allowed Vietnam’s fresh lychee to be imported into developed countries (such as Korea, ...); The state/province cooperates with donors and businesses in trade promotion activities in potential export markets for Vietnamese lychee and fruit products (Japan, Korea, US, EU, ASEAN…).